Pemberdayaan Ibu Hamil dalam Mencegah Anemia di Desa Penyengat Olak Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi 2021 - Lia Artika Sari; Enny Susilawati; Evrina Solvia Soleh (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Globally, 52% of pregnant women in developing countries are anemic. This figure is greater than the rate of anemia in pregnant women in industrialized countries which is only 20%. The countries with the highest prevalence of anemia were India (88%), followed by Africa (50%), Latin America (40%) and the Caribbean (30%). The WHO report in 2008, the incidence of anemia in Southeast Asia was 48.2%, Indonesia was ranked 58th with an anemia rating of 44.3% in pregnant women. This community service activity is in the form of HB checks, counseling on the impact of anemia and pregnant women can use the compliance application to consume blood-added tablets in Penyengat Olak Village, Jambi Luar Kota, Muaro Jambi Regency in 2021. The results of this community service are a minimum HB level of 7.3 g/dl and a maximum of 11.2 g/dl before using the compliance monitoring application to consume FE tablets, the implementation of counseling on the impact of anemia on pregnant women in Penyengat Olak Village in 2021 to 30 pregnant women, as many as 24 (80%) respondents were obedient in consuming FE tablets and levels Minimum HB 7.6 gr/dl and maximum 12.2 gr/dl after using the compliance monitoring application taking FE tablets. It is hoped that this community service activity can increase the knowledge of pregnant women about anemia in pregnancy, increase the compliance of pregnant women in consuming FE tablets, and increase the HB levels of pregnant women who obediently consume FE tablets.